Fat Requirements in Pregnancy and Infancy - Laitinen Kirsi (Royal Society Of Chemistry, 2022)
Fats are important during pregnancy and infancy not only as energy sources but also as structural components of cellular membranes and precursors of bioactive signaling compounds. Fats and particularly long-chain polyunsaturated fatty acids (LC-PUFA) are crucial for fetal and infant tissue development and organogenesis, and may also play a role in the future health of the infant, i.e. in the child's neurodevelopment and his/her risk of developing a range of diseases such as allergic diseases. The mother–placenta–fetus interaction and the related adaptive and regulatory mechanisms ensure optimal fetal growth and development. These processes may be influenced by maternal dietary intakes and body composition during pregnancy and breastfeeding, and again by the dietary intake of the infant. Reference values have been set for dietary intake of fats for each of these periods, i.e. pregnancy, breastfeeding, and infancy.
Fats and Associated Compounds